IMPLEMENTASI PENANGANAN GELANDANGAN DAN PENGEMIS TERHADAP KETERTIBAN UMUM DI KOTA SERANG - Siti Kamila Khaerunnisa; Rokilah Rokilah (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2024)
Serang City is one of the areas that has social problems, in this case the presence of homeless people and beggars which is quite disturbing for public order. In an effort to deal with this, it has been regulated in Serang City Regional Regulation Number 2 of 2010 concerning Prevention, Eradication, Management of Disease and Society, However, if you look at the current reality, there is no visible decrease in the number of homeless people and beggars on the streets, in fact homeless people and beggars are increasing every year. This research aims to determine and analyze the implementation of handling homeless people and beggars on public order in Serang City in accordance with Regional Regulation Number 2 of 2010 and to find out and analyze sanctions for regulating public order towards homeless people and beggars in Serang City. This research uses a qualitative method in the form of observing phenomena that occur in society in depth. This type of research uses empirical juridical, an approach based on data obtained directly from the community as the first source through field research, which is carried out either through observations, interviews. as well as by reviewing statutory regulations. The results of this research show that: (1) Regional Work Units have not implemented the Regional Regulations optimally so that there has not been a reduction in the number of homeless people and beggars, (2) Existing sanctions in accordance with the applicable Regional Regulations have not been implemented for homeless people and beggars